A Framework for Biosafety Implementation: Report of a Meeting - McLean, Morven A. (International Service for National Agricultural Research, 2003)
Concern over possible environmental and health implications of modern biotechnology has stimulated regulatory mechanisms for food safety and environmental risk assessment. Given the challenges and difficulties inherent in building these regulatory systems and the needed operating capacities, the ISNAR convened an international expert consultation in July 2001 titled ""A Framework for Biosafety Implementation: A Tool for Building Capacity."" The present report provides an overview of the main building blocks used to develop a conceptual framework for biosafety implementation. It includes (1) plenary papers summarizing lessons and experiences from national, regional, and global efforts to build biosafety capacity; (2) a ""strawman"" framework for implementing biosafety that was extensively reviewed and modified during the consultation; and (3) the collective wisdom of participants in the consultation who contributed to the development of the conceptual framework, as summarized in the working-group synopses.